Quantifying Managerial Ability in the Shipping Industry - Georgiou, Despina (q, 2018)
The current thesis evaluates the managerial ability for 10 shipping companies stated worldwide, for a 6 year period between 2012 and 2017. For that purpose, the DEA technique is used, which has extensively been used before for measuring the efficiency of various aspects of the company. Although managerial ability has been estimated in various studies for a variety of different sectors and firms it has never before been applied specifically to the shipping sector across different firms worldwide. Moreover, after applying the DEA method, regression models are utilized in order to estimate how various firm-specific variables can affect the manager availability. The findings indicated that the results regarding the efficiency of the managers vary depending on the DEA model that has been applied.
Keywords: Managerial ability; Shipping companies stated worldwide; DEA technique